Woody Allen: o teatro em seus filmes, o cinema em suas peças - Myriam Pessoa Nogueira (2014)
We tried to analyse the plays and screenplays of Woody Allen the film diretor, actor, also a playwright and storyteller; we searched for a reciprocal influence by the cinema on his plays and by the theater on his films, since intertextuality quotations of various artistic works, until adaptations from his own work to another media; we analyzed his parodies, and the influences by other authors on his style, and also his influence on the style of new authors. Through this, we want to understand the presence of the filmic language in the writing of his plays, and the role played by the dramatic language in his cinematographic narrative.